A probabilistic method to forecast the international migration of Mexico by age and sex - GARCÍA-GUERRERO, Víctor Manuel (Papeles de Población, 2016)
In this paper a method to model and forecast international immigration, emigration and net migration by age and sex is proposed. This method is based on Lee’s 1993 model, which is an extension of the well-known Lee-Carter model (Lee & Carter, 1992). The method proposed allows forecasting migration consistently with the whole population dynamic in the sense that it incorporates sustainable migration levels. This sustainability is incorporated through a logistic transformation of total migration, and it allows constraining the migration’s fluctuation and thus avoiding negative values in a total population forecast. The method is applied to recent estimates of Mexican immigration, emigration and net migration by age and sex from 1960 to 2010 made by the Mexican Society of Demography (SOMEDE, 2011). The predictive power of the model is tested forecasting the period 1991 to 2010 and comparing the results with estimates for such period.